2012
DOI: 10.1155/2012/219319
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Affects Nitric Oxide Synthases and Improves Renal Outcome in a Rat Model of Severe Ischemia/Reperfusion Injury

Abstract: Background. Nitric oxide (NO)-signal transduction plays an important role in renal ischemia/reperfusion (I/R) injury. NO produced by endothelial NO-synthase (eNOS) has protective functions whereas NO from inducible NO-synthase (iNOS) induces impairment. Rosiglitazone (RGZ), a peroxisome proliferator-activated receptor (PPAR)-γ agonist exerted beneficial effects after renal I/R injury, so we investigated whether this might be causally linked with NOS imbalance. Methods. RGZ (5 mg/kg) was administered i.p. to SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
1
22
0
3
Order By: Relevance
“…The present results were consistent with other experimental studies that demonstrated that TZDs are beneficial for renal and cardiovascular protection (13,18,22,23). ROG intervention attenuated hyperuricemia, which is generally acknowledged as an independent risk factor of CKD.…”
Section: Discussionsupporting
confidence: 93%
“…The present results were consistent with other experimental studies that demonstrated that TZDs are beneficial for renal and cardiovascular protection (13,18,22,23). ROG intervention attenuated hyperuricemia, which is generally acknowledged as an independent risk factor of CKD.…”
Section: Discussionsupporting
confidence: 93%
“…18,25 After treatment with NGAL, rats showed down-regulated Cc3 protein compared with I/R þ NS rats. Caspases are intracellular proteases family that regulate programmed cell death, and the activation of the caspase family is a key part in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification protocol and primers were used as recently described [2,7,8] Quantification was performed using the ΔΔC T method using β-actin as reference gene and expression in control cells was normalized to 1.…”
Section: Methodsmentioning
confidence: 99%
“…The organic anion transport system of the renal proximal tubule plays a crucial role in the excretion of a variety of potentially toxic compounds [1,2,3,4,5,6,7,8,9,10]. This system consists of organic anion exchangers located at the basolateral membrane that represent the rate determining step of elimination and the efflux step through the apical membrane [11,12].…”
Section: Introductionmentioning
confidence: 99%